Analytical and clinical performance of the Advansure i3 procalcitonin assay. (2nd November 2021) - Heo, Wonyoung; Park, Hyung-Doo
Abstract: Procalcitonin (PCT) is a clinically useful biomarker for early diagnosis and subsequent management of sepsis. We evaluated the analytical performance of a new automated chemiluminescent immunoanalyzer-based procalcitonin assay, AdvanSure i3 PCT assay (LG Life Sciences, Korea) on an AdvanSure i3 (LG Life Sciences) and compared it to the Elecsys BRAHMS PCT assay (Roche, Switzerland) on a Cobas e801 (Roche). Analytical performance was performed for the precision, linearity, and method comparison with the Elecsys BRAHMS PCT assay by Clinical and Laboratory Standards Institute guidelines. Clinical evaluations were conducted using 87 residual samples from admitted patients with suspected infection. The patients were classified based on Sepsis-3 classification. The AdvanSure i3 PCT assay exhibited a CV <5.5% for between-run precision and <6.5% for within-laboratory precision. The assay was linear up to 80.32 µg/L ( r = 0.990). Statistical analysis showed that the two assays yielded a good correlation ( r = 0.996), with a weighted kappa value of 0.94. Median plasma PCT level was significantly different between the non-sepsis and sepsis groups ( p < .001) and the non-sepsis and septic shock groups ( p < .0018). The AdvanSure i3 PCT assay showed good analytical performance and correlation with the Elecsys BRAHMS PCT assay for the sepsis patients. This new assay can be used as a diagnostic early marker of sepsis in clinical laboratories.